High‐Throughput Raman‐Activated Cell Sorting in the Fingerprint Region. Issue 10 (9th April 2022) - Lindley, Matthew; Gala de Pablo, Julia; Peterson, Walker; Isozaki, Akihiro; Hiramatsu, Kotaro; Goda, Keisuke
Abstract: Cell sorting is the workhorse of biological research and medicine. Cell sorters are commonly used to sort heterogeneous cell populations based on their intrinsic features. Raman‐activated cell sorting (RACS) has recently received considerable interest by virtue of its ability to discriminate cells by their intracellular chemical content, in a label‐free manner. However, the broad deployment of RACS beyond lab‐based demonstrations is hindered by a fundamental trade‐off between throughput and measurement bandwidth (i.e., cellular information content). Here this trade‐off is overcome and broadband RACS in the fingerprint region (300–1600 cm −1 ) with a record high throughput of ≈50 cells per second is demonstrated. This represents a 25× throughput increase compared to previous demonstrations of broadband fingerprint‐region RACS outside the resonance Raman regime. To show the utility of the RACS, real‐time label‐free sorting of microalgal cells based on their accumulation of carotenoids and polysaccharide granules is demonstrated. These results hold promise for medical, biofuel, and bioplastic applications. Abstract : Here high‐throughput broadband Raman‐activated cell sorting (RACS) in the fingerprint region (300–1600 cm −1 ) with a record high throughput of ≈50 cells per second, a 25× throughput increase compared to previous demonstrations of broadband fingerprint‐region RACS without resonance Raman enhancement, is realized. Real‐time label‐free sorting of microalgal cells based on their accumulation of carotenoids and polysaccharide granules is demonstrated.